Dynamic Behavior of Aggregated Buildings With Different Floor Systems and Their Finite Element Modeling - Stavroulaki, Maria E. (Frontiers in Built Environment, 2019)
The aim of this research is to propose a way of simulating the interaction between aggregated masonry buildings for the finite element analysis. In most cases, the stiffness of adjacent structures is difficult to evaluate due to the unavailability of data on unknown geometry, parameters, materials, and so on; therefore, a parametric study was essential to simulate the restrictions which are developed. The first results of this research are presented in the present paper, through two case studies wherein rod elements or elastic foundations are proposed for the support of an adjacent structure. The natural frequencies of the real building complex are estimated by the finite element modeling of all the structures, which is then used for the dynamic identification of the simplified model. The experimental measurements of the natural frequencies and modes of the building which are studied could be used for the dynamic identification of the finite element model.